Male Fertility: Facts, Distribution and Drivers of Inequality - Bernt Bratsberg; Andreas Kotsadam; Selma Walther (Institute of Labor Economics (IZA), 2021)
We document new facts on the distribution of male fertility and its relationship with men's labor market outcomes. Using Norwegian registry data on all births since 1967, we show that rates of male childlessness in recent cohorts are 72% among the lowest five percent of earners but only 11% among the highest earners, and that this gap widened by almost 20 percentage points over the last thirty cohort years. There has been a compression in the fertility distribution, with a substantial share of men being "left behind" and fewer men experiencing a larger share of the population's new births. We use firm bankruptcies as a source of variation in job loss and earnings to provide robust evidence that men experiencing negative labor market shocks are less likely to experience the birth of a child, transition out of childlessness, and be partnered, and that these effects are persistent up to 15 years after the event. We conclude by documenting that men's fertility penalty to job loss has increased markedly over the last three decades.
Keywords: J12; J13; 330; male fertility; unemployment; inequality